HISTORY, AESTHETICS AND PATHOLOGY: SADNESS AS A FORM OF THOUGHT IN PAULO PRADO - Lúcio de Carvalho Diniz, Cláudio (Revista Gênero e Interdisciplinaridade, 2025)
This article proposes a critical analysis of Paulo Prado's "Portrait of Brazil" (1928), considering it as an essay in which melancholy operates as an explanatory category of Brazilian national identity. Drawing on the articulation of cultural history, psychoanalysis, and literature, the article investigates how Prado transforms collective sadness into a structuring symptom of the Brazilian character, marked by inherent vices, greed, lust, and miscegenation, and exacerbated by 19th-century Romantic ideology. Melancholy is understood here not only as an emotional state but also as a form of thought, permeating both the psychology of the author and that of his social class—the declining São Paulo coffee aristocracy. The work is situated between the tradition of nineteenth-century racialism and the modernist aesthetics of the 1920s, composing a pessimistic narrative that interprets Brazil as a failed nation still in search of symbolic redemption. The analysis seeks to highlight the tensions, contradictions, and ambivalences in Prado's work, highlighting its originality as a portrait of an elite in ruin and a country in an identity crisis.